2021
DOI: 10.1038/s41535-021-00394-7
|View full text |Cite
|
Sign up to set email alerts
|

Universal size-dependent nonlinear charge transport in single crystals of the Mott insulator Ca2RuO4

Abstract: The surprisingly low current density required for inducing the insulator to metal transition has made Ca2RuO4 an attractive candidate material for developing Mott-based electronics devices. The mechanism driving the resistive switching, however, remains a controversial topic in the field of strongly correlated electron systems. Here we probe an uncovered region of phase space by studying high-purity Ca2RuO4 single crystals, using the sample size as principal tuning parameter. Upon reducing the crystal size, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The 4d layered perovskite ruthenate Ca 2 RuO 4 is known as a Mott insulator in which the temperature-induced metal-insulator transition appears at 357 K in bulk crystals, [32] and the nonthermal, purely electronic insulator-to-metal transition driven by current has also been demonstrated in bulk crystals [33][34][35][36][37][38][39][40][41][42][43] and epitaxial thin films. [44] Unlike other materials with nonthermal-type transitions, remarkably, the presence of nonequilibrium metallic and insulating phases (called L* and S*), which are distinctive from the phases in the temperature-driven transition under electronic equilibrium, has been observed for bulk Ca 2 RuO 4 under current densities of >4 A cm −2 in structural characterizations [37,38,40] and Raman spectroscopy measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The 4d layered perovskite ruthenate Ca 2 RuO 4 is known as a Mott insulator in which the temperature-induced metal-insulator transition appears at 357 K in bulk crystals, [32] and the nonthermal, purely electronic insulator-to-metal transition driven by current has also been demonstrated in bulk crystals [33][34][35][36][37][38][39][40][41][42][43] and epitaxial thin films. [44] Unlike other materials with nonthermal-type transitions, remarkably, the presence of nonequilibrium metallic and insulating phases (called L* and S*), which are distinctive from the phases in the temperature-driven transition under electronic equilibrium, has been observed for bulk Ca 2 RuO 4 under current densities of >4 A cm −2 in structural characterizations [37,38,40] and Raman spectroscopy measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Materials with metal-insulator phase transitions have been considered particularly promising for device applications because of the highly reliable high-operation-speed conductivity changes in the materials driven by the transitions. 1,2) By applying electric fields or injecting currents, a variety of nonlinear transport properties have been demonstrated in the materials with metal-insulator transitions, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and important application functions have been derived from the transport nonlinearity. In principle, materials with metal-insulator phase transitions show sharp resistive switching 4,5,8,10,12,14,17,18,[20][21][22][23] and negative differential resistance (NDR) [3][4][5][6][7][8][9][10][11][13][14][15][16]…”
Section: Introductionmentioning
confidence: 99%
“…24) The layered orthorhombic perovskite Ca 2 RuO 4 is known as a representative platform for this class of metal-insulator transitions. 5,6,9,10,[12][13][14][15]21,25) In the currentvoltage characteristics of Ca 2 RuO 4 , clear nonlinear transport phenomena (both switching and NDR) have been observed based on the current-driven transition, 5,6,9,10,[12][13][14][15]21) and because of the nonthermal origin of the transition, the driving mechanisms have been indicated to be not predominated by thermal runaway due to Joule heating but by current injection itself, 9,14,21) unlike those in materials such as VO 2 . In the nonlinear transport phenomena, additionally, previous studies have demonstrated that the unit cell dimensions of Ca 2 RuO 4 progressively and continuously change with current injection (and with progression of the current-induced transition), originating from the strong electron-lattice coupling in the material.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we apply this method to the layered Mott insulator Ca 2 RuO 4 single crystal with the orthorhombic crystal structure. [9][10][11][12][13] Recent studies on this material have reported interesting conduction phenomena including nonlinear conduction, [14][15][16][17][18][19][20][21][22][23] but the fundamental in-plane (abplane) anisotropy has not been investigated so far. To investigate the detailed origin of such unusual transport behavior in orthorhombic Ca 2 RuO 4 , it is also essential to study the in-plane transport anisotropy.…”
Section: Introductionmentioning
confidence: 99%